Hydroxychloroquine – Beyond Malaria: Its Role in Rheumatology and COVID-19 – A Literature Review - Adam Jan Ząbek; Jakub Paweł Kuźniar; Emilia Gabriela Chrzanowska; Michalina Zagalska; Marta Turek; Tomasz Tamborski; Adam Grzebinoga; Julia Szlążek; Iwona Pudełko; Barbara Roguska (Journal of Education, Health and Sport)
Hydroxychloroquine (HCQ) is a long-established drug, initially used to treat malaria and later widely applied in autoimmune diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). As an immunomodulatory agent, HCQ plays a crucial role in managing chronic inflammation. Despite its benefits, its use requires monitoring due to potential adverse effects, including retinopathy and myopathy.[1]